2017
DOI: 10.1139/facets-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

“An Be Jigi”: Collective cooking, whole grains, and technology transfer in Mali

Abstract: This paper addresses how available resources, food security, technology, and culture are shaping the choices rural Malian women are making to ensure the health, energy, and well-being of their families. This research contributed to evaluating an eight-year research project (An Be Jigi) targeting improved nutrition. The study, performed over four months, used semi-structured interviews of 120 women in six villages in Mali to assess the identified issues with qualitative and quantitative approaches. This paper d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…The role of benefit-driven motivation in adoption is acknowledged in the NSA literature. Several articles refer to motivational factors, such as better nutrition and health, enhanced coping mechanisms for food and nutrition security, empowerment, comparative advantages of promoted crops, and income opportunities [ 47 , 49 – 51 ]. However, while we found that the improved nutritional status of children was a key catalyst, others remarked that nutrition and health benefits may not be sufficient drivers for adoption [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of benefit-driven motivation in adoption is acknowledged in the NSA literature. Several articles refer to motivational factors, such as better nutrition and health, enhanced coping mechanisms for food and nutrition security, empowerment, comparative advantages of promoted crops, and income opportunities [ 47 , 49 – 51 ]. However, while we found that the improved nutritional status of children was a key catalyst, others remarked that nutrition and health benefits may not be sufficient drivers for adoption [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specific women's trials furthermore triggered changes in selection strategy to explicitly focus on adaptation to low soil-phosphorus, a problem that is most acute for women farmers (Leiser et al 2012;. In addition, nutrition research and varietal-monitoring for nutritional value was integrated into the collaborative breeding work as a result of women's involvement and focus on both grain quality as well as yield (Isaacs et al 2018;Rattunde et al 2018;Bauchspies et al 2017). Thus, several organizational structures have enabled women's roles and agency in the network to grow and make critical contributions to its functioning.…”
Section: Organizational Models and Structuresmentioning
confidence: 99%
“…Biofortified millet varieties could be promoted in the future together with appropriate information to producers and consumers, if they proved to increase iron and zinc intakes in the same conditions of consumption. In Mali, a recent study showed the high acceptability of whole grain foods prepared from biofortified sorghum varieties, based on information about its improved iron content (34). In India, acceptability of iron and zinc biofortified pearl millet, despite lower scores at hedonic tests compared to conventional pearl millet, was estimated as good enough to further integrate these biofortified varieties into an efficacy study (21).…”
Section: Resultsmentioning
confidence: 99%